Constructive analysis on teaching architecture through face to face and online learning - Saraoui, Selma; Attar, Abdelghani; Khadraoui, Mohamed Amine (Technium Social Sciences Journal, 2022)
A couple of decades now, online learning has gained some popularity among scholars to work across borders and use time efficiently. However, the advent of world pandemic that resulted in a big health crisis has spurred more interest to keep going with the online classes close the gap between students and their teachers. We present here a professional experience that we had in our architecture department during the Covid-19 period. This worth sharing experience has to explain the pedagogical content set in the training unit and will likewise emphasize the importance of “subject project workshop” used in the discipline of architecture. Our contribution in the light of this paper is to come up with suggestions likely to enhance the practice of teaching using modern resources.